DataSheet_1_Preclinical Assessment of IgY Antibodies Against Recombinant SARS-CoV-2 RBD Protein for Prophylaxis and Post-Infection Treatment of COVID-19.docx - Agurto-Arteaga, Andres (2022)
Within the framework of the current COVID-19 pandemic, there is a race against time to find therapies for the outbreak to be controlled. Since vaccines are still tedious to develop and partially available for low-income countries, passive immunity based on egg-yolk antibodies (IgY) is presented as a suitable approach to preclude potential death of infected patients, based on its high specificity/avidity/production yield, cost-effective manufacture, and ease of administration. In the present study, IgY antibodies against a recombinant RBD protein of SARS-CoV-2 were produced in specific-pathogen-free chickens and purified from eggs using a biocompatible method. In vitro immunoreactivity was tested, finding high recognition and neutralization values. Safety was also demonstrated prior to efficacy evaluation, in which body weight, kinematics, and histopathological assessments of hamsters challenged with SARS-CoV-2 were performed, showing a protective effect administering IgY intranasally both as a prophylactic treatment or a post-infection treatment. The results of this study showed that intranasally delivered IgY has the potential to both aid in prevention and in overcoming COVID-19 infection, which should be very useful to control the advance of the current pandemic and the associated mortality.